Analisa Energi Furnace 101-H-2 Paska Turn Arround 2017 Pertamina Refinery Unit II Sei. Pakning - Dian Putra Satria; Romy Romy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Furnace is a heating equipment for petroleum processing, which requires the largest operational costs in the processing business. During the first quarter of 2019 Pertamina II of the total raw materials used amountedto 10.16% for processing energy needs of which 75% of the energy consumed by the furnace. Furnaces that are operated with optimal conditions will result in savings in operational costs. Analysis of furnaces has been carried out by analyzing energy efficiency after Turn Around in 2019 and comparing it with data before Turn Around in 2017. As a result, efficiency was obtained after Turn Around in 2019 by 97% and before Turn Around in 2017 at 68% -75%. It was known that when TA-2017 has been carried out a total replacement of tubes,castables, and stacks or repairs of the mayor. Meanwhile, when TA-2019 was carried out repairs and cleaning or minor repairs.Keywords: furnace, energy. efficiency, crude oil, residue